Blindness following bilateral neck dissection. A case report and review of the literature. (2020) - Krasnikova, Alexandra; Kreutzer, Kilian; Angermair, Stefan; Heiland, Max; Koerdt, Steffen
Highlights: Postoperative vision loss is a rare and devastating complication in head and neck surgery. Blindness can also occur after modified radical neck dissection. Patients undergoing high-risk procedures should have to be informed that there is a risk of vision loss. This complication should be highlighted in the standard declaration of consent. Abstract: Introduction: Visual loss is a very rare but dramatic complication of such an indispensable standard procedure in head and neck tumor surgery such as the cervical lymphadenectomy (neck dissection). Presentation of case: We present a review of the literature and a new case of a postoperative blindness of a 65-year-old man with type 2 diabetes who underwent a unilateral radical neck dissection, a contralateral modified radical neck dissection and a hemimandibulectomy for an oropharyngeal squamous cell carcinoma. Discussion: By now there have been only 15 clinical cases of total blindness published during the last 60 years. In 13 cases blindness followed a bilateral radical neck dissection whereas in 2 cases blindness occurred after a combined selective and modified radical neck dissection. Ischemia of the optic nerve due to intraoperative hypotension, blood loss and venous congestion were the major etiological aspects of blindness. Perioperative management of differentiated volume and blood administration, blood pressure management and a close postoperative ophthalmological check seem to be of a major importance for prevention and early detection of visual deterioration. Nevertheless, there are no clear predicative factors for blindness after neck dissection and the prognosis is unfavorable. Conclusion: Even though postoperative vision loss is a rare and devastating complication, this current case and the review of the literature show that it occurs every once in a while following standard operations to the head and neck. Patients undergoing high-risk procedures should have to be informed that there is a slight risk of perioperative vision loss and this should be highlighted in the standard declaration of consent.